2008
DOI: 10.1007/bf03393060
|View full text |Cite
|
Sign up to set email alerts
|

How Kids Learn to Say the Darnedest Things: The Effect of Multiple Exemplar Instruction on the Emergence of Novel Verb Usage

Abstract: . We would like to acknowledge the assistance of the children and staff at the CABAS® Schools where these experiments were conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
15
0
3
Order By: Relevance
“…Findings and interpretations from all of the work suggested possible interventions to induce verbal capabilities in children who were missing them. The interventions have consisted of multiple-exemplar instruction across listener and speaker responses (Fiorile & Greer, 2007;, saying and writing (Greer, Yuan, et al, 2005), contextual establishing-operations control for manding and tacting (Nuzzolo-Gomez & Greer, 2004), contextual control for literal and metaphoric expressions (Meincke-Matthews, 2005), and contextual control for suffixes (Greer & Yuan, 2008;Speckman & Greer, 2006). Other interventions included conditioning reinforcement of stimuli for the range of observing responses (Dinsmoor, 1983;Donahoe & Palmer, 2004;Keohane, Greer, & Ackerman, 2006a, 2006b, 2006cLongano & Greer, 2006;Tsai & Greer, 2006) that resulted in accelerated learning and developmental cusps that were not capabilities, yet seem to be foundational cusps that prepare the potential for capabilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings and interpretations from all of the work suggested possible interventions to induce verbal capabilities in children who were missing them. The interventions have consisted of multiple-exemplar instruction across listener and speaker responses (Fiorile & Greer, 2007;, saying and writing (Greer, Yuan, et al, 2005), contextual establishing-operations control for manding and tacting (Nuzzolo-Gomez & Greer, 2004), contextual control for literal and metaphoric expressions (Meincke-Matthews, 2005), and contextual control for suffixes (Greer & Yuan, 2008;Speckman & Greer, 2006). Other interventions included conditioning reinforcement of stimuli for the range of observing responses (Dinsmoor, 1983;Donahoe & Palmer, 2004;Keohane, Greer, & Ackerman, 2006a, 2006b, 2006cLongano & Greer, 2006;Tsai & Greer, 2006) that resulted in accelerated learning and developmental cusps that were not capabilities, yet seem to be foundational cusps that prepare the potential for capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, whereby children seem to acquire language seemingly without direct instruction, has led some, but not all, linguists to posit innate psychological language constructs, and discount the role of learning, based on anecdotal descriptions of emergent language (Pinker, 1999). Of course, now that Naming and other verbal capabilities have been shown to be the result of experimentally isolated experiences, these construct theories seem to have less face validity (Barnes-Holmes et al, 2005;Feliciano, 2006;Fiorile & Greer, 2007;Gilic, 2005;Greer, Nirgudkar, & Park, 2003;Greer & Yuan, 2008;Miguel et al, 2008).…”
Section: Cusps That Are New Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuzzolo‐Gomez and Greer's () findings have been replicated across participants of different ages (e.g., 3 to 7 years of age), with typically and atypically developing children (Luke, et al, ), children with autism (Nuzzolo‐Gomez & Greer, ; Eby et al, ), bilingual children (Luke et al, ), and across verbal topographies (e.g., taking dictation and vocal spelling, Eby et al, ; Greer, Yuan & Gautreaux, ; regular and irregular past tense verbs, Greer & Yuan, ; noun and adjective forms containing suffixes ending in ‘‐er’ , Speckman et al, ). Further comparisons of the differential effectiveness of SEI and MEI (Eby et al, ; Greer & Yuan, ; Speckman et al, ) are consistent with previous research, showing that emergence was not observed until participants received MEI.…”
Section: Application and Significance Of Meimentioning
confidence: 88%
“…Other studies reporting the use of reinforcement procedures to bolster grammaticality also appeared around this time (e.g., H. B. Clark & Sherman, 1975;Garcia, 1974;Garcia & Batista-Wallace, 1977;Garcia, Guess, & Byrnes, 1973;Hester & Hendrickson, 1977;Heward & Eachus, 1979;Martin, 1975;Sailor, 1971;StevensLong & Rasmussen, 1974) and during the ensuing decades (e.g., Charlop, Schreibman, & Thibodeau, 1985;Chase, Ellenwood, & Madden, 2008;Greer & Yuan, 2008;Hernandez, Hanley, & Ingvarsson, 2007;Secan, Egel, & Tilley, 1989;Whitehurst & ValdezMenchaca, 1988;Wulfert & Hayes, 1988).…”
Section: Mythmentioning
confidence: 94%